2013
DOI: 10.3109/02688697.2013.835378
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a prospective multi-centre audit of chronic subdural haematoma management in the United Kingdom and Ireland

Abstract: BACKGROUND. Chronic subdural haematoma (CSDH) is a common condition that increases in incidence with rising age. Evacuation of a CSDH is one of the commonest neurosurgical procedures; however the optimal peri-operative management, surgical technique, post-operative care and the role of adjuvant therapies remain controversial. AIM. We propose a prospective multi-centre audit in order to establish current practices, outcomes and national benchmarks for future studies. METHODS. Neurosurgical units (NSU) in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…For example, in the multi-centre prospective observational CSDH cohort study of the British Neurosurgical Trainee Research Collaborative [7], data on 1205 patients with CSDH were collected from 26 of the 33 UK and Ireland neurosurgical units between May 2013 and January 2014. The project was driven by trainees and supported by consultants in all participating units [2]. The study found that a subdural drain was used in 85% of patients, while according to the 2006 survey 85% surgeons in the UK and the Republic of Ireland would either never use or use drains in less than a quarter of burr hole drainage operations [11]; this confirms the substantial uptake of the Cambridge CSDH trial findings across the UK [1].…”
supporting
confidence: 65%
“…For example, in the multi-centre prospective observational CSDH cohort study of the British Neurosurgical Trainee Research Collaborative [7], data on 1205 patients with CSDH were collected from 26 of the 33 UK and Ireland neurosurgical units between May 2013 and January 2014. The project was driven by trainees and supported by consultants in all participating units [2]. The study found that a subdural drain was used in 85% of patients, while according to the 2006 survey 85% surgeons in the UK and the Republic of Ireland would either never use or use drains in less than a quarter of burr hole drainage operations [11]; this confirms the substantial uptake of the Cambridge CSDH trial findings across the UK [1].…”
supporting
confidence: 65%
“…In addition, there was a lack of adequate statistical power to detect a significant difference in the clinical outcomes. Therefore, caution is advised in interpreting these results, and a further larger prospective study is warranted to confirm these findings [9]. Other authors have reported that the preoperative baseline cognitive status has a significant impact on the surgical decision making [22].…”
Section: Limitationsmentioning
confidence: 86%
“…The study protocol was approved by the Academic Committee of the Society of British Neurological Surgeons (SBNS) and has been published previously. 7 The study was supported by the SBNS and formed part of the Neurosurgical National Audit Program.…”
Section: Participants and Study Settingsmentioning
confidence: 99%